THE COMBINATION OF INFRARED AND CONTRACT RELAX STRETCHING SHOWED NO SIGNIFICANT DIFFERENCE AS COMBINATION OF INFRARED AND DEEP TRANSVERSE FRICTION TO REDUCE OF NECK DISABILITY TENSION-TYPE HEADACHE CONDITION AMONG CIVIL STATE APPARATUS AT GOVERNOR’S OFFICE IN - Mirawati, Komang Sri; Dewi, Anak Ayu Nyoman Trisna Narta; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 2 (2017): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Persistent contraction of the muscles of the neck will causes neck disability so it can be tension-type headache.The purpose of this study was to compare the combination of infrared and contract relax stretching with the combination of infrared and deep transverse friction to the decrease of neck disability in tension-type headache condition. This research is experimental with pre-test and post-test group design. The sample of research are 28 people divided into two groups. Group 1 was given combination of infrared and contract relax stretching while group 2 was given combination of infrared and deep transverse friction. Measurement of neck disability is using  Neck Disability Index( NDI)  . Hypotension tested in each group using Paired sample t-test was obtained p = 0.000 for group 1 and p = 0.000 for group 2. The result showed that at each groups had a significant decrease in neck disability. To compare the results of the decrease of neck disability after intervention using Independent sample t-test in both groups obtained p = 0.741 (p> 0.05). The conclusion is the combination of infrared and contract relax stretching showed no significant difference as combination of  infrared and deep transverse friction to the reduce of neck disability with tension-type headache conditions. A deep transverse friction can be used if the patient wants a more comfortable when given intervention and very recommended for client that loss of understanding.   Keywords: infrared, contract relax strtching, deep transverse friction, neck disability index ( NDI), tension type-headache.